Isolation of streptomyces sp. From lapindo mud soil, sidoarjo, east java province, indonesia as a larvicide candidate against aedes aegypti - Yotopranoto, Subagyo; Kurnijasanti, Rochmah; Rohmah, Etik Ainun (Folia Medica Indonesiana, 2017)
Streptomyces sp. is a bacterium that can live in many kind of habitations e.i. marine, sea sponge, coastal area, soil, desert soil, river bank etc. Many antibiotics and secondary metabolites are produced by this bacterium. Several secondary metabolites of the bacterium can be used as an insecticide against insects including mosquito larva.The purpose of this study was to search and isolate until species of Streptomyces sp. from Sidoarjo Lapindo mud soil in East Java province that can be used as a larvicide against Aedes aegypti larva, the dengue haemorrhagic fever vector.The method of study was to collect several mud soil samples from Sidoarjo Lapindo. The collected samples were cultured in ISP-4 media for producing mix-cultures. Then, to isolate the suspected colony of Streptomyces sp. by culturing again in several replications on ISP-4 media in petri-dish. The pure isolates were cultured in ISP-4 slant media. There were could be obtained eight pure isolates of Streptomyces sp.The characterization of 16S rRNA of Streptomyces sp. was done in order to determine the species. DNA isolation was done and followed by DNA sequencing, then compared to Gene Bank with BLAST program. The results showed that the sequence nucleotide bases of Streptomyces Sp-D6 had high similarity to Streptomyces sp. 171524, beside the sequence nucleotide bases of Streptomyces Sp-D7 and Sp-D9 had high similarity to Strepto-myces sp. ACT-01578 and ACT-175695. These three species can be used as larvicide candidate against Ae. aegypti.